Manejo Integrado de picudo negro (cosmopolite sordidus germar) en el cultivo de banano (musa AAA). - Torres Lamilla, José Jasmany (2019)
SUMMARY This paper examines the role of integrated management, which proposes using all methods of control, to keep the population of a pest below the threshold of economic damage, through the research of books and authors of theses related to the management of the black weevil plague (cosmopolite sordidus germar) in banana cultivation, the analyzed data show that for the control of this insect it can be done using a trap or also making a natural preparation with hot pepper water, boiling between 15 and 20 minutes and then apply on the plant among others suggest to let act natural predators such as the coleoptera hololepta sp and allegory dilatata that are predators of larva and egg also indicates that the ant of genus Camponotus sp can be found frequently in banana plantations predating black weevil larvae have shown that they can control a lot in the attack of this pest According to some investigations to obtain a better control of black weevil, a chemical control should be carried out mainly, using nematicides with insecticide activity applied at the base of the mat. This is the most widespread method for the control of black weevil chemical control measures have also been established with the use of traps, placing some type of insecticide as a means to reduce the boll weevil population. The growing demand for bananas for export, has caused farmers to opt for the use of high impact insecticides such as Carbofuran and Clorpiriphos. Given the high populations of existing picudo insecticide applications have to be repeated throughout the year in order to this way to have a better control of the attack of the weevil in the plantation and in this way obtain a better production and productivity.